AKUMULASI LOGAM KROMIUM (Cr) DALAM SEDIMEN, AKAR DAN DAUN MANGROVE Avicennia marina DI MUARA SUNGAI BADUNG - Suwandewi, A. A. Sg. Istri A.; Eka Suprihatin, Iryanti; Manurung, Manuntun (Jurnal Kimia (Journal of Chemistry); Vol. 7, No. 2 Juli 2013DO - 10.24843/JCHEM.2013.v07.i02.p09, 2013)
Research on Cr metal content in the sediment, roots and leaves of the Avicennia marina in estuary of Badung river has been conducted. This study was aimed to determine the ability of Avicennia marina in accumulating chromium from the ecosystem where the plant grows. The concentrations of Chromium were determined by the use of Atomic Absorption Spektrcophotometer followed by a calibration standard method. The results showed that the roots of the Avicennia marina accumulated Cr metal most. Total concentrations of  Cr  metal in leaves was 0,9579 mg/kg and in the roots was 1,9680 mg/kg, while in the sediment 0,4536 mg/kg. Based on the amount of metal accumulation in the roots and leaves of mangrove, it can be suggested that the Avicennia marina was capable of accumulating Cr present in the ecosystem.
Keywords: mangrove, Avicennia marina, Cr metal